On a unique identification of 3D features between BIM and GIS for 3D Cadastre - Janečka Karel; Vaněk Martin (Reports on Geodesy and Geoinformatics)
The recent research has demonstrated both the potential of building information management (BIM) for the 3D cadastre, especially for legal spaces of building units and the advantage of the combination of physical and legal boundaries for their visualization. During the lifetime cycle of the building and the units within, the geometry of units can change. Then, it is necessary to promote the transition from the updated BIM model to connected systems. Considering this, the paper focuses on a unique identification of building units between BIM and GIS. The main idea is that each feature (in our case, the building unit) receives a unique identifier when it is created, which is then used in every system during its life cycle. Each of these domains has its own specific technical requirements for the unique identification. The aim is to have just one identifier of the building unit regardless of the selected information system to make an effective update. The paper further aims to model the 3D legal spaces of building units using BIM and their storage inside the external spatial database based on the CityGML standard data model. The proposed solution facilitates the storage of the 3D legal spaces of building units together with their physical counterparts in one environment based on the widely recognized OGC standard. Furthermore, as many countries still use 2D parcel-based cadastre, the proposed solution also allows for the connection of the existing cadastral information systems with these externally stored 3D legal spaces without the necessity of changing the systems.